MOTIVASI IRAN MEMBUKA KEMBALI KANTOR KEDUTAAN BESAR DI INGGRIS TAHUN 2015 - ", Alfajri; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research focuses on the motivation of Iran to reopen the Office of the Embassy in the UK in 2015. The closure of the Iranian embassy and the British started from the attack protesters against the Office of the British Embassy in Iran. Britain has imposed a number of sanctions and embargo against Iran over its nuclear development. Iranian diplomacy in obtaining freedom nuclear development achieved during the reign of President Hassan Rouhani through the Joint Action of Geneva of Interim Agreement on Iran's Nuclear Program which was attended by Britain, France, China, USA, Russia and Germany (P5+1). The results of this agreement known as the Joint Comprehensive Plan of Action (JCPOA). This research used of journals, books, and websites. The theory used in this research is National Interest in Realism perspective. Level of analysis is National State. This research explain that Iran's efforts to reopen the Office of the Embassy in the UK is to obtain the removal of sanctions of Iran and to restore the confidence of the international community related to Iran's nuclear program. Keyword: Embassy, National Interest, Nuclear, NPT (Non-Proliferation Treaty)